China's Economic Strategy Confronts U.S. Intervention Through Taiwan - Wahyu Gusriandari; Guntur Eko Saputro; Lukman Yudho Prakoso (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
East Asia has a region full of conflict dynamics, especially the spotlight to date, namely the conflict between China and Taiwan which is increasingly heated, the intervention of the United States and its ambitious strategy further aggravates the conflict between China and Taiwan. Especially with the conflict between Russia and Ukraine which has caused more turmoil because China does not want to condemn the actions taken by Russia so that the United States provides security assistance for Taiwan. so that it wants to discuss how China's strategy in dealing with the intervention of the United States through Taiwan will maintain China's sovereignty which can occur at any time there can be war and China will fight for one China policy to awaken China's power from the threat of the United States, and using qualitative descriptive research seeks to explain in detail and the structure of problems that occur in conflict between China and Taiwan.